Pengembangan Bidang Kewanitaan Jama’ah Masjid di Jatipunggur Lengkong Nganjuk - Ristianah, Niken (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
This research aims to describe the knowledge development of the feminine field of the mosque of Al Amin, Jatipunggur Lengkong Nganjuk. Based on the fact that there is a village, most of the population is the livelihood of farmers and the level of public education that productive age tends to still be low. Especially knowledge of the fundamentals of religion. In this research authors use a type of descriptive research with the approach of Asset Based Community Development (ABCD). The results showed that the knowledge development of femininity for the mosque and community in Jatipunggur Lengkong Nganjuk Village has been able to be implemented well through workshop activities. Workshop participants participated in all series of activities, ranging from listening to the delivery of the material by the speakers, discussing about the realistic and actual feminist problems in the community, especially mothers and young women worshippers